Digital Learning, Life Satisfaction, and Perceived Stress Due to COVID-19 Emergency: Case Study Among Female Saudi University Students - Mabrouk, Fatma; Mekni, Mohamed Mehdi; Aldawish, Aishah (Frontiers in Psychology, 2022)
The paper explores the impact of the corona virus disease-19 (COVID-19) pandemic on the Saudi higher education system. The research focuses on the relationship between digital learning in COVID-19 time, life satisfaction, and stress among female students. The study discusses measures, practices, defense mechanisms, and coping strategies to face challenges. Using an online survey based on psychological effects and its role in defense mechanisms and coping strategies, findings show that digital learning provides flexibility in terms of time and offers resources at a lower cost compared to traditional learning. In addition, results show that the coping strategy perception is higher in obtaining a good score and succeeding than to get over the pandemic and recovering from the illness itself. Finally, results confirm that a positive attitude influences positively life satisfaction.